Gambaran Daya Bunuh Larvasida Ekstrak Daun Pare (Momordica charantia L.) dengan Metode Infudasi dan Metode Maserasi - Izza Ratna Kumala (Akademi Analis Kesehatan Pekalongan, 2023)
Culex sp. is one of the insects as a vector of chronic filariasis disease. Filariasis are often found in tropical countries such as Indonesia so its presence needs to be controlled. One of the controls that can be done is by killing the larvae with natural larvicides made by infudsion and maceration methods. This study aims to determine the description of mortality of Culex sp. larvae after being given natural larvicides, namely bitter melon leaf extract with certain concentration levels. Descriptive research was conducted with samples of Culex sp. larvae taken from a ditch which is the original habitat. This study was repeated 6 times and observation of larvae mortality at 24 hours after administration of the extract. The extract was made into 4 concentration levels, namely 1%, 5%, 10% and 15%. The four concentrations obtained results that the maceration method effectively kills 100% of Culex sp larvae at a concentration of 5% while the infusion method requires a concentration of >15% so that all larvae can be killed. This can occur because in the infusion method the bioactive compounds do not diffuse optimally so that the levels of bioactive compounds as larvicides are also lower than the maceration method.